2017
DOI: 10.1093/jxb/erx331
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular localization and interactions among rubber particle proteins from Hevea brasiliensis

Abstract: The major proteins of rubber particles from Hevea brasiliensis associate with the endoplasmic reticulum membrane and can interact with the key cytosolic biosynthetic enzyme cis-prenyltransferase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 26 publications
3
27
0
3
Order By: Relevance
“…Yamashita et al (2016) reported that a protein complex, consisting of HRT1, REF, and HRT1-REF BRIDGING PROTEIN in the ER, constitutes the biosynthetic machinery for natural rubber. It is known that in H. brasiliensis rubber particles originate from the ER (Shi et al, 2016), which was further confirmed by Brown et al (2017). Together, we concluded that Eu-rubber biosynthesis could occur in the ER also.…”
Section: Discussionsupporting
confidence: 82%
“…Yamashita et al (2016) reported that a protein complex, consisting of HRT1, REF, and HRT1-REF BRIDGING PROTEIN in the ER, constitutes the biosynthetic machinery for natural rubber. It is known that in H. brasiliensis rubber particles originate from the ER (Shi et al, 2016), which was further confirmed by Brown et al (2017). Together, we concluded that Eu-rubber biosynthesis could occur in the ER also.…”
Section: Discussionsupporting
confidence: 82%
“…Even so, the presence of helix 8 is unique and its function is worth further investigation. A possibility might be association with cell membrane or membrane-bound anchoring proteins, because AbUPPS lacks the extended N-terminus as observed, for example, in rubber synthase (Brown et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it also has many other functions, such as calcium homeostasis (Hong et al ., 1999), oil and protein body formation (Huang, 1996; Herman, 2008), rubber particle formation (Brown et al ., 2017) and auxin regulation (Friml & Jones, 2010; Kriechbaumer et al ., 2015). …”
Section: Introductionmentioning
confidence: 99%
“…As the first biosynthetic organelle in the plant secretory pathway, the endoplasmic reticulum (ER) underpins the production, folding and quality control of proteins (Brandizzi et al, 2003;Hawes et al, 2015), as well as lipid biosynthesis (Wallis & Browse, 2010). In addition, it also has many other functions, such as calcium homeostasis (Hong et al, 1999), oil and protein body formation (Huang, 1996;Herman, 2008), rubber particle formation (Brown et al, 2017) and auxin regulation (Friml & Jones, 2010;Kriechbaumer et al, 2015).…”
Section: Introductionmentioning
confidence: 99%